Soliton solutions of NLSE with quadratic-cubic nonlinearity and stability analysis - Aslan, Ebru Cavlak; İnç, Mustafa (Taylor & Francis Ltd, 2017)
In this article, we investigate exact soliton solutions of nonlinear Schrodinger equation (NLSE) with quadratic-cubic nonlinearity. The Jacobi elliptic functions are employed to study optical solitons. Dark and bright solitons are obtained. Also, the stability analysis of dark and bright solitons for the NLSE with quadratic-cubic nonlinearity is considered.
Keywords: Bright